Purification of Indole Contained in Wash Oil by Combination of Extraction and Crystallization (Part 1: Recovery and Concentration of Indole Contained in Wash Oil by Solvent Extraction) - Su Jin Kim (Molecules, 2022)
For the purpose of determining the high-purity purification of indole (IN) contained in wash oil in concentrations of 5.75%, this study, first of all, investigated the concentration of IN contained in wash oil using a combination of methanol extraction to recover IN in the wash oil, and n-hexane re-extraction to concentrate IN present in the extract phase, recovered through methanol extraction. In order to examine the effect of each operation on the recovery and concentration of IN contained in the wash oil, batch 1-stage and batch co-current 5-stage distribution equilibrium was performed simultaneously. As 5-stage equilibrium extraction and re-extraction progressed, the recovery rate of IN decreased to about 79.1%, while IN composition in the raffinate phase recovered by re-extraction was highly concentrated to about 73.3%. From the high recovery rate and composition of IN obtained through this study, we confirmed that the combination examined by this study was one of the very useful combinations for the concentration of IN present in the wash oil. Furthermore, we reviewed the recovery and concentration process of IN contained in the wash oil using the experiment results of the extraction and the re-extraction obtained from this study.